A CASE OF METHANOL INTOXICATION COMPLICATED WITH ACUTE PANCREATITIS, ALCOHOLIC KETOACIDOSIS, AND INTRACEREBRAL HEMORRAGE - Rahardi, Eric; Moda Arsana, Putu (journal of internal medicine, 2011)
Methanol intoxication occurs after accidental or suicidal ingestion occasionally and the toxicity is due to the formationof formaldehyde and formic acid. Methanol ingestion can also lead to acute pancreatitis, a sudden in! ammation of thepancreas, and high metabolic acidosis as a complication. Brain injury in methanol intoxication could be ischemia orhemorrhage form. Therefore we?d like to present a report a male with methanol intoxication with several complicationsuch, acute pancreatitis, alcoholic ketoacidosis, and CVA-ICH. The patient presented with hemodynamic instability andsevere metabolic acidosis with pH 6.991. The anion gap was 30 mmol/l. Amylase was 187 U/l and CT scan showed intracerebralhemorrhage at right fronto temporo parietal lobe with peri-focal edema (volume 48 cc). Patient unfortunatelydied three days later after force discharge by his families. Brain injury in methanol toxicity is characterized by lesionsaffecting both basal ganglia and subcortical regions. The lesion could be ischemia/necrosis or hemorrhage, selectivelyaffecting the putamenal bilaterally.